MANAGING PROJECTS - Boddy David (Prentice Hall, 2002)
PROJECTS AND ORGANISATIONS UNDERSTANDING PROJECT MANAGEMENT MANAGING THE PROJECT TEAM MANAGING BEYOND THE TEAM
PROJECTS AND ORGANISATIONS UNDERSTANDING PROJECT MANAGEMENT MANAGING THE PROJECT TEAM MANAGING BEYOND THE TEAM